1985
DOI: 10.1007/bf00327241
|View full text |Cite
|
Sign up to set email alerts
|

Gene amplification in Djungarian hamster cell lines possessing decreased plasma membrane permeability for colchicine and some other drugs

Abstract: By multistep selection a set of clones and sublines possessing different levels of resistance to colchicine or adriablastin was obtained from the SV40-transformed Djungarian hamster cell lines, DM-15 and DMcap. Resistance to both colchicine and adriablastin is associated with an alteration of plasma membrane permeability leading to a decreased uptake of various drugs (3H-colchicine, 3H-cytochalasin B, 3H-actinomycin D, 3H-puromycin, 3H-vinblastine, 14C-chloramphenicol). The DNA of cells highly resistant to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The average number of DMs per cell displayed a close correlation with the level of colchicine resistance as has similarly been observed in vincristine-resistant MAZ mouse tumor cells (Meyers et al, 1985) and C-46 murine neuroblastoma cells (Baskin et al, 1981). DMs are indicative of gene amplification Schwab et al, 1983) and based on hybridization studies published by Roninson et al (1984) and Gudkov et al, (1985), multi-drug resistant cells contain amplified DNA sequences. Thus the decrease in the average number of DMs per cell suggests a decrease in the dosage of DNA sequences which encode resistance-specific proteins.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The average number of DMs per cell displayed a close correlation with the level of colchicine resistance as has similarly been observed in vincristine-resistant MAZ mouse tumor cells (Meyers et al, 1985) and C-46 murine neuroblastoma cells (Baskin et al, 1981). DMs are indicative of gene amplification Schwab et al, 1983) and based on hybridization studies published by Roninson et al (1984) and Gudkov et al, (1985), multi-drug resistant cells contain amplified DNA sequences. Thus the decrease in the average number of DMs per cell suggests a decrease in the dosage of DNA sequences which encode resistance-specific proteins.…”
Section: Discussionsupporting
confidence: 68%
“…DMs are indicative of gene amplification Schwab et al, 1983) and based on hybridization studies published by Roninson et al (1984) and Gudkov et al, (1985), multi-drug resistant cells contain amplified DNA sequences. Thus the decrease in the average number of DMs per cell suggests a decrease in the dosage of DNA sequences which encode resistance-specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“…6A), pMDR1 hybridized to mRNA in both human and mouse cell lines, whereas at higher stringency (Fig. 6B) (20), and Gudkov et al (14) suggested that the gene encoding multidrug resistance in Chinese hamster ovary (CHO) cells could be transferred from hamster to mouse L cells by DNA-mediated gene transfer and that this transfer correlates with increased expression of a 170-kilodalton membrane glycoprotein (8,20). However, the nature of the gene(s) transferred in these experiments has not yet been demonstrated at the DNA level.…”
Section: Methodsmentioning
confidence: 79%
“…This problem has been studied in tissue culture through the development of rodent and human cell lines which express simultaneous resistance to many drugs, such as colchicine, vinblastine, doxorubicin hydrochloride (Adriamycin; Adria Laboratories Inc.), and actinomycin D (3,4,16). By use of the technique of in-gel renaturation (21), it has been possible to clone DNA sequences, designated mdr, that are commonly amplified in various hamster (13,14,22) and human (11,23,24) multidrug-resistant cell lines. The cloned human DNA sequence mdrl is expressed at high levels as a 4.5-kilobase (kb) mRNA in several different human multidrugresistant cell lines (23,24).…”
mentioning
confidence: 99%
“…This problem has been studied in tissue culture through the development of rodent and human cell lines which express simultaneous resistance to many drugs, such as colchicine, vinblastine, doxorubicin hydrochloride (Adriamycin; Adria Laboratories Inc.), and actinomycin D (3,4,16). By use of the technique of in-gel renaturation (21), it has been possible to clone DNA sequences, designated mdr, that are commonly amplified in various hamster (13,14,22) and human (11,23,24) multidrug-resistant cell lines. The cloned human DNA sequence mdrl is expressed at high levels as a 4.5kilobase (kb) mRNA in several different human multidrugresistant cell lines (23,24).…”
mentioning
confidence: 99%